A COMPARATIVE STUDY OF RE1-SILENCING TRANSCRIPTION FACTOR (REST) OF TELEOST FISHES - Panda, Subhamay; SUVRANIL PODDAR (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Repressor element 1 (RE1)-silencing transcription factor (REST) is a zinc-finger transcription factor or else can be called as neuron- restrictive silencer factor primarily described as a negative regulator of nuclear differentiation at present known to play key function in neuronal cells. Methods: With this initial note the aim of this study was to determination of protein sequence level characteristics of REST of Japanese pufferfish (Takifugu rubripes) and channel catfish (Ictalurus punctatus) with the help of different bioinformatical research tools. Results: There was no instance of any signal signature present within the amino acid sequence of studied REST molecules. In the present research work protein multiple sequence alignment represented in polarity coloring scheme demonstrates variable sites and as well as conserved sites of proteins in Japanese pufferfish and channel catfish. Conclusion: The current research analysis clearly manifests that protein evolution occurred within the REST of Japanese pufferfish (Takifugu rubripes) and channel catfish (Ictalurus punctatus). Keywords: Repressor element 1-silencing transcription factor, Teleost fishes, Japanese pufferfish, Channel catfish, Sequence analysis.